2017
DOI: 10.1007/s00270-017-1791-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Advanced HCC Treated with Radioembolization: Comparing Impact of Clinical Performance Status Versus Vascular Invasion/Metastases

Abstract: Patients classified as BCLC C due to ECOG PS 1 demonstrated longer survival when compared to those presenting with PVT, metastases and/or ECOG PS 2. Hence, ECOG PS 1, as an isolated variable, may not be a true indicator of advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…Of these, 234 articles were excluded on the basis of their titles and abstract and 54 potentially eligible full-text articles were assessed according to the eligibility criteria. Seventeen studies met the eligibility criteria and were included in the analysis (89101113192021222324293031323334).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 234 articles were excluded on the basis of their titles and abstract and 54 potentially eligible full-text articles were assessed according to the eligibility criteria. Seventeen studies met the eligibility criteria and were included in the analysis (89101113192021222324293031323334).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported radioembolization data (19202133), ten reported sorafenib data (891011132930313234), and three compared both treatments using a retrospective approach (222324). Among the studies investigating radioembolization, four used glass-based intra-arterial vectors (19202233), two used resin-based vectors (2324), and one used both (21). Six studies were prospective (131929323334), and eleven were retrospective (89101120212223243031).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limitations include the single‐center nature of the analysis without a comparator. Also, survival data in advanced HCC attributed by ECOG 1 may have been overestimated . Strengths include that this represents the largest single‐center prospective cohort of Y90, with sample size and follow‐up permitting meaningful analyses that compensate for heterogeneity of lesion size and liver function.…”
Section: Discussionmentioning
confidence: 99%